2021
DOI: 10.15581/004.42.001
|View full text |Cite
|
Sign up to set email alerts
|

Competencia emocional en docentes de Infantil y Primaria y estudiantes universitarios de los Grados de Educación Infantil y Primaria

Abstract: El estudio, descriptivo-correlacional, evalúa la competencia emocional de docentes de Infantil y Primaria y de estudiantes universitarios de los Grados de Educación Infantil y Primaria. Se contó con una submuestra de 92 docentes y otra de 290 estudiantes. La competencia emocional se defi nió operacionalmente a partir de dos indicadores: meta- estados de ánimo y empatía cognitiva-afectiva. Los resultados revelan que el nivel de desarrollo en la mayoría de los componentes de la competencia emocional estudiados s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 29 publications
(39 reference statements)
1
13
0
1
Order By: Relevance
“…The factor displaying the highest levels of emotional intelligence amongst the infant and primary education teachers in our study is emotional regulation, followed by emotional understanding and, finally, emotional perception. These data are similar to those published by Cazalla-Luna and Molero [ 31 ], Domínguez and Nieto [ 7 ] and Schoeps et al [ 43 ], Martínez-Saura et al [ 21 ] found that infant and primary education teachers exhibited high levels of emotional perception, then emotional regulation and, finally, emotional understanding. Suárez and Martín [ 2 ] reported that teachers in higher education obtained more significant levels in emotional understanding, then in emotional regulation and, finally, in emotional perception.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The factor displaying the highest levels of emotional intelligence amongst the infant and primary education teachers in our study is emotional regulation, followed by emotional understanding and, finally, emotional perception. These data are similar to those published by Cazalla-Luna and Molero [ 31 ], Domínguez and Nieto [ 7 ] and Schoeps et al [ 43 ], Martínez-Saura et al [ 21 ] found that infant and primary education teachers exhibited high levels of emotional perception, then emotional regulation and, finally, emotional understanding. Suárez and Martín [ 2 ] reported that teachers in higher education obtained more significant levels in emotional understanding, then in emotional regulation and, finally, in emotional perception.…”
Section: Discussionsupporting
confidence: 90%
“…Socioemotional education should be implemented in the classroom by teaching staff themselves, since more effective results are achieved than with programs or activities led by non-academic staff [ 15 , 16 , 17 ]. Teaching staff should therefore be the first to receive socioemotional education [ 18 , 19 , 20 , 21 ], since this would provide them with an effective model for handling socioemotional skills when they are with their students [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations